Pengaruh Kadar Logam Berat Pb, Cr dan Cd Pada Air Limbah Setelah Pengolahan Hasil Desain Tim Pengolah Limbah Lab Terpadu UII - Yusuf Habibi (Integrated Lab Journal, 2020)
Research has been done for effect of heavy metals lead, chrom and cadmium in waste water after processing from UII Integrated Laboratory waste water processed team design, determination with Atomic Absorbtion Spectrophotometer. Waste water processed team design used filter like sponge and palm fiber, absorbent as activated carbon and kaolin. Result of heavy metals determination after processed show that lead down 17%, chrom down 100% and cadmium is not detected.